Making Space for Community-Based Practice Experience and Spirit in the Academy: Journeying Towards the Making of an Indigenous Academic - Johnson, Shelly (First Peoples Child & Family Review, 2013)
This narrative recounts four experiences of an Indigenous social work academic employed at a mainstream university in Canada. These experiences include: (1) valuing community-based practice and spiritual experiences prior to entering the academy; (2) learning in an Indigenous doctoral cohort; (3) using Indigenous knowledge during the hiring process into a tenure-track faculty position in a mainstream university; and, (4) including Indigenous knowledge to secure academic research grant applications, and to meet teaching, scholarly, and service expectations. Finally, this narrative identifies systemic academic issues from the perspectives of four other Indigenous and women academics of colour, and teachings that may assist new Indigenous faculty entering mainstream university employment.